Reshaping the air power RMAF participation in LIMA, 1991-2015
The Royal Malaysian Air Force involvement with Langkawi International Maritime and Aerospace started since 1991. With these series of LIMA exhibitions we have witnessed the progressively more involvement of the RMAF in makin it a successful and well regarded event of international standards.